New treatment perspectives in autism spectrum disorders - Yuri Bozzi (Frontiers Research Topics, 2015)
Developing novel and more effective treatments that improve quality of life for individuals with autism spectrum disorders is urgently needed. To date a wide range of behavioral interventions have been shown to be safe and effective for improving language and cognition and adaptive behavior in children and adolescents with ASD. However many people with ASD can receive additional benefit from targeted pharmacological interventions. One of the major drawback in setting up therapeutics intervention is the remarkable individual differences found across individuals with ASD. As a matter of fact the medications that are currently available address only symptoms associated with ASD and not the core domains of social and communication dysfunction. The pathogenesis paradigm shift of ASD towards synaptic abnormalities moved the research to pathway to disease that involve multiple systems and that are becoming the forefront of ASD treatment and are pointing toward the development of new targeted treatments. Some new therapeutics have been tested and others are being studied. In this context single gene disorders frequently associated with ASD such as Rett Syndrome, Fragile X and Tuberous Sclerosis have been of significant aid as neurobiology of these disorders is more clear and has a potential to shed light on the altered signaling in ASD. However much research is needed to further understand the basic mechanisms of disease and the relationship to idiopathic ASD. Clinical trials in children are underway with agents directed to core symptoms and to the associated disorders in the search of new therapeutics and progress are expected with possible new option for therapeutics in ASD in the upcoming future. Children and Adolescents with ASD and their families can provide important information about their experience with new treatments and this should be a priority for future research. In addition, research performed on genetic mouse models of ASD will keep on providing useful information on the molecular pathways disrupted in the disease, thus contributing to identify novel drug targets.